Research on Comprehensive Evaluation Model of Physical Education Teaching Quality Based on Multivariate Data - Ruitao Li; Chunhua Du; Wei Du; Yuanchun He; Ping Zhang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Because of the complexity of the factors affecting the quality of teaching has obvious, lead to the larger error in the results of the assessment. Therefore, put forward the physical education teaching quality comprehensive evaluation model based on multivariate data research. Using the analytic hierarchy process (AHP) to build the physical teaching quality evaluation mechanism, based on the relative importance of data, establish compound consistency check of judgment matrix. The weights were assigned according to the importance of the data, and the weighted results were equally divided by the method of pulling apart grades. Finally, the physical education teaching quality was evaluated based on AHP-ISD model. The experimental results show that the accuracy of the method can reach more than 97%, which is obviously better than the method of comparison